A drought rarity and evapotranspiration-based index as a suitable agricultural drought indicator. (November 2017) - Zhao, Huan; Xu, Zongxue; Zhao, Jie; Huang, Wen
Highlights: An integrated agricultural drought index (IADI) was proposed. The IADI was developed combining agricultural drought severity and rarity. The IADI was tested for agricultural drought monitoring in Northeast China. This index developing framework could be extended to other drought indicators. Abstract: Agricultural drought has a substantial impact on crop yields and, thus, food security within the context of global climate change. Therefore, efforts should focus on agricultural drought detection and monitoring. Agricultural drought is identified as unusually dry conditions in which severe water stress impedes crop growth. Thus, the crop water deficit severity and rarity are both key factors in agricultural drought detection and are rarely considered simultaneously in existing drought indices. To overcome this limitation, an integrated agricultural drought index (IADI) based on drought rarity and evapotranspiration is proposed. As an important grain production base, Northeast China has suffered from frequent droughts in recent years, demonstrating an urgent need for accurate drought monitoring. In this study, the superiority of the IADI as an agricultural drought indicator through the detection of the severity and rarity was tested using the drought disaster area (DDA) and grain yield, and its performance was compared to that of the evaporative drought index (EDI), an indicator that accounts for only the water deficit severity. The response of agricultural drought to meteorological drought and its impact on the grain yield were further analyzed. The results showed that (1) the IADI can effectively capture the drought variability and identify drought events by combining the detection of the severity and rarity. (2) The R 2 value between the DDA and IADI (0.72) was higher than that with the EDI (0.50), and the same result was found in a comparative analysis using the grain yield, showing that the IADI is a suitable indicator for agricultural drought assessment. (3) Severe and extreme meteorological droughts and extreme agricultural droughts in western Jilin and western Liaoning were more frequent than in other regions, highlighting the agricultural drought tendency and sensitivity to precipitation deficit in this region. (4) The impacts of agricultural drought on grain yield in three provinces of Northeast China vary greatly during the crop-growing period, with the most significant impacts occurring from May to July. Therefore, this period represents the critical crop water requirement period, and timely irrigation should be ensured during this period.